2020
DOI: 10.15184/aqy.2020.61
|View full text |Cite
|
Sign up to set email alerts
|

Love and hope: emotions, dress accessories and a plough in later medieval Britain, c. AD 1250–1500

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…At Buckden, the coulter was surrounded by grain-rich fills (charred rye, barley and wheat), which further emphasizes the relationship between plough and life. At Alnhamsheles, although later than much of the evidence discussed here, the deposition of a coulter beneath a building in the fifteenth century coincided with a period of poor harvests, and it is suggested that it was offered in response to events that would have devastated a community (Standley, 2020). Further evidence of the importance of the plough within a community comes from the use of plough-irons in trials, where they were used as a tool to provide fair justice (Standley, 2020, 753;Thomas et al, 2016, 754).…”
Section: Symbolic Valuementioning
confidence: 82%
See 2 more Smart Citations
“…At Buckden, the coulter was surrounded by grain-rich fills (charred rye, barley and wheat), which further emphasizes the relationship between plough and life. At Alnhamsheles, although later than much of the evidence discussed here, the deposition of a coulter beneath a building in the fifteenth century coincided with a period of poor harvests, and it is suggested that it was offered in response to events that would have devastated a community (Standley, 2020). Further evidence of the importance of the plough within a community comes from the use of plough-irons in trials, where they were used as a tool to provide fair justice (Standley, 2020, 753;Thomas et al, 2016, 754).…”
Section: Symbolic Valuementioning
confidence: 82%
“…Nonetheless, finds of medieval coulters likely to come from mouldboard ploughs have been found in England. The earliest is a seventh-century find from Lyminge, Kent, but others come from Buckden, Cambridgeshire (eighth-to ninth-century), Scraptoft, Leicestershire (tenth-century) and Alnhamsheles, Northumberland (fifteenth-century) (Connor and Billington, 2021;Leahy, 2013;Standley, 2020;Thomas et al, 2016).…”
Section: Use Of Draught Cattle In Medieval Englandmentioning
confidence: 99%
See 1 more Smart Citation
“…The social value of early heavy plough technology that enabled increased production of previously uncultivated heavy, clay soils, is implied by the ritual deposition of implements such as coulters throughout Northwest Europe in the medieval period [ 79 , 80 ]. Some recognition of the importance of cattle within a community may also be evident in the deliberate burial of the lower legs of an animal in a mid-tenth to mid-eleventh century boundary ditch at Ketton, Northamptonshire [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…Emotion can be materialized through words on the scripts, textiles, or ornaments, which could be defined as evidence of communication and intensification of emotion. Thus, in archaeological settings, the emotional interpretation has to use material evidence to reconstruct emotions through reading the emotional meaning of objects and practices, such as artifacts and specific patterns (Standley, 2020;Tarlow, 2000Tarlow, , 2012. In human behavior, the love and the desire for love often embody the whole spectrum of human emotions.…”
Section: Introductionmentioning
confidence: 99%